Insulin secretagogue fraction of Argyrolobium roseum - Ahmed, Zabeer (Array, 2008)
Summary: Argyrolobium roseum Cambers Jaub & Spauch;Papilionaceae, is a sexually reproducing, rare, annual herb that grows in tropical and sub-temperate tracts of the north-western Himalayan region of the Indian subcontinent; it has neither been documented for treating diabetes mellitus nor any other biological activity is attributed to this herb. Its ethanolic extract (KA-030) exhibited antihyperglycemic effect in oral glucose tolerance test and streptozotocin treated Wistar rats.This extract was further fractionated into petroleum ether (KA-131), chloroform (KA-132), butanolic (KA-133) and aqueous (KA-134) fractions. Of these fractions, KA-133 evoked a dose dependent stimulation of insulin secretion in the in vitro (RINm5F cells) and in vivo models when compared with glibenclamide. These results demonstrate the presence of natural antidiabetic and insulin secreting; product(s) in Argyrolobium roseum. A pure principle characterized as vitexin has been isolated from KA-133 fraction and when evaluated for in vitro insulin; secretion showed a dose dependent insulin secretagogue activity. Chemical data depict vitexin as a major compound in KA-133. However, further isolation of more pure molecules, their chemical characterization and bioevaluation have been carried out separately. Subacute toxicity and preclinical general pharmacological studies conducted on ethanolic extract proved it as safe and free from any adverse effect on gross behavior and general body system up to a dose of 2000 mg/kg p.o